2005
DOI: 10.30638/eemj.2005.035
|View full text |Cite
|
Sign up to set email alerts
|

Reactors for Application in Heterogeneous Photocatalysis

Abstract: The present paper is a literature survey of some representative works conducted in the filed of photocatalytic reactors approaching the major issues should be considered in development of commercially available photocatalytic systems for different purposes: whether to use suspended or supported catalysts and whether to use concentrated or nonconcentrating sunlight. Different photoreactor configurations and experimental setups containing such systems used for study of varied liquid-phase or gas-phase pollutants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Trends observed in the process of photocatalytic degradation of synthetic textile effluent with different types of catalysts were as follows ( Maximum degradation took place when Ag-TiO 2 (mesh) (UV 400W) is used as compared to TiO 2 , because of the slow combination of electron hole pair and large surface area of the mesh [35,19]. When titanium dioxide (TiO 2 ) is radiated with intensity of band gap energy (3.2Ev), it generates electrons of band (eCB)-and hoes in valance band (hVB)+.…”
Section: Effects Of Different Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Trends observed in the process of photocatalytic degradation of synthetic textile effluent with different types of catalysts were as follows ( Maximum degradation took place when Ag-TiO 2 (mesh) (UV 400W) is used as compared to TiO 2 , because of the slow combination of electron hole pair and large surface area of the mesh [35,19]. When titanium dioxide (TiO 2 ) is radiated with intensity of band gap energy (3.2Ev), it generates electrons of band (eCB)-and hoes in valance band (hVB)+.…”
Section: Effects Of Different Catalystsmentioning
confidence: 99%
“…Birnie et al [34] have extensively reviewed the photocatalytic reactors currently in use. Caliman and Balasanian [35] and Serrano et al [36] have reported the performance of the reactor as a function of its dimension. However, photocatalytic reactors that provide better configuration to maximize efficiency of photon utilization are considered suitable [37][38][39].…”
mentioning
confidence: 99%